PEMBERDAYAAN IBU RUMAH TANGGA NELAYAN MELALUIPELATIHANDIVERSIFIKASI PRODUK PERIKANAN DAN KELEMBAGAAN DI KELURAHAN MALABERO KOTA BENGKULU - Hari Laksamana; Ferry Ro'is; Deri Syahputra; Alfita Shirat Firdausiyah; Reswita Reswita (Universitas Bengkulu, 2018)
Malabero in Teluk Segara Bengkulu City is one of the villages mostly located in the coastal area and facing directly to beach or ocean. Most of the people work as fishermen who depend on their catch in the sea. This is quite a concern for the academics in seeing a phenomenon where there are still problems and opportunities that can be developed and at this time has not been developed by the fishing community. The problems and opportunities are the quality of products produced through the economic activities of the community in the form of fishery products. It can be happen and can’t be separated from human resource problem that exist in coastal area in managing natural potency and manage effort properly. To provide solutions to these problems it is important for students as intellectual generation to implement creative economic empowerment for the community, especially housewives in Malabero Village.Activities undertaken in this activity are the provision of new business groups and institutional strengthening for target communities, providing training in the scope of entrepreneurship in the field of fishery processing, packaging training in accordance with standards for products in the area. The implementation of this activity for the community benefit consists of knowledge development, management and of course in utilizing the existing resources in the coastal region as a potential economic sector in a sustainable.Keywords: empowerment, housewives of fishermen, coastal areas